Effectiveness of Online Mindfulness-Based Interventions on Psychological Distress and the Mediating Role of Emotion Regulation - Ma, Ying; She, Zhaozhuo; Siu, Angela Fung-Ying; Zeng, Xianglong; Liu, Xinghua (Frontiers in Psychology, 2018)
Online mindfulness-based intervention as a feasible and acceptable approach has received mounting attention in recent years, yet more evidence is needed to demonstrate its effectiveness. The primary objective of this study was to examine the effects of online mindfulness-based programs on psychological distress (depression and anxiety). The randomized controlled intervention design consisted of four conditions: group mindfulness-based intervention (GMBI), self-direct mindfulness-based intervention (SDMBI), discussion group (DG) and blank control group (BCG). The program lasted 8 weeks and a total of 76 participants completed the pre- and post-test. Results showed that participants in GMBI and SDMBI had significant pre- and post-test differences on mindfulness, emotion regulation difficulties, and psychological distress, with medium to large effect sizes. In addition, ANCOVA results indicated significant effects of group membership on post-test scores of mindfulness, depression and anxiety when controlling the pretest scores, with medium to large effect sizes. The GMBI appeared to exert the greatest effects on outcome variables in comparison with other groups. In addition, changes in emotion regulation difficulties across groups could mediate the relationship between changes in mindfulness dimensions (Observing and Describing) and changes in psychological distress across groups. These results provided encouraging evidence for the effectiveness of online mindfulness-based interventions in reducing psychological distress, and the possible mediating role of emotion regulation, while also underlining the importance of group discussion in online mindfulness-based interventions.